1996
DOI: 10.1901/jeab.1996.66-97
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Delay, Not Ratios, Control Choice in Concurrent Chains

Abstract: In two experiments, pigeons were trained with concurrent‐chains schedules, wherein responding to equal initial links measured preference between variable‐interval terminal links. Absolute terminal‐link duration was varied by keeping constant the difference between the terminal‐link delays and forcing their ratio to change. Delay‐reduction theory scales value relative to a common temporal context and requires that delay differences control choice. Thus, preference should remain invariant. Most competing account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
33
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 30 publications
2
33
1
Order By: Relevance
“…Their initial links were identical VI 60-s schedules, and their terminal links were pairs of VI schedules that always differed by a mean of 20 s. For example, in one condition the two terminal links were VI 5 s and VI 25 s, and in another condition the two terminal links were VI 100 s and VI 120 s. Savastano and Fantino found no systematic changes in preference as long as the difference between the two terminal links was kept constant at 20 s. More recently, Fantino and Goldshmidt (2000) obtained similar results in a series of experiments with pigeons that used a very different procedure-a foraging analogue called the successive-encounters procedure. Savastano and Fantino (1996) showed that this finding, the constant-difference effect, was inconsistent with several different mathematical models of choice, including melioration theory (Vaughan, 1985), incentive theory (Killeen & Fantino, 1990), and Davison's (1988) extension of the hyperbolic decay model. Each of these models predicts that preference for the shorter terminal-link schedule should decrease toward indifference as the durations of the terminal-link schedules become longer.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Their initial links were identical VI 60-s schedules, and their terminal links were pairs of VI schedules that always differed by a mean of 20 s. For example, in one condition the two terminal links were VI 5 s and VI 25 s, and in another condition the two terminal links were VI 100 s and VI 120 s. Savastano and Fantino found no systematic changes in preference as long as the difference between the two terminal links was kept constant at 20 s. More recently, Fantino and Goldshmidt (2000) obtained similar results in a series of experiments with pigeons that used a very different procedure-a foraging analogue called the successive-encounters procedure. Savastano and Fantino (1996) showed that this finding, the constant-difference effect, was inconsistent with several different mathematical models of choice, including melioration theory (Vaughan, 1985), incentive theory (Killeen & Fantino, 1990), and Davison's (1988) extension of the hyperbolic decay model. Each of these models predicts that preference for the shorter terminal-link schedule should decrease toward indifference as the durations of the terminal-link schedules become longer.…”
mentioning
confidence: 92%
“…Although the constant-difference effect may be counterintuitive, Savastano and Fantino (1996) showed that it is predicted by Fantino's (1969) delay-reduction theory. In its simplest form, delay-reduction theory can be expressed as follows:…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Concurrent-chain schedules have proven to be useful evaluative tools, and they have helped to distinguish among competing theories of choice (e.g., Fantino, 1969;Grace, 1994;Mazur, 2000Mazur, , 2001Savastano & Fantino, 1996). However, nearly all of the published research on concurrent-chain schedules has reported only steadystate performance, collected after subjects had been exposed to the same schedules for many daily sessions.…”
mentioning
confidence: 99%